An Emerging Role for Post-translational Modifications in Regulating RNP Condensates in the Germ Line - Schisa, Jennifer A.; Elaswad, Mohamed T. (Frontiers in Molecular Biosciences, 2021)
RNA-binding proteins undergo regulated phase transitions in an array of cell types. The phase separation of RNA-binding proteins, and subsequent formation of RNP condensates or granules, occurs during physiological conditions and can also be induced by stress. Some RNP granules have roles in post-transcriptionally regulating mRNAs, and mutations that prevent the condensation of RNA-binding proteins can reduce an organism’s fitness. The reversible and multivalent interactions among RNP granule components can result in RNP complexes that transition among diffuse and condensed states, the latter of which can be pathological; for example, in neurons solid RNP aggregates contribute to disease states such as amyotrophic lateral sclerosis (ALS), and the dysregulation of RNP granules in human germ cells may be involved in Fragile X-associated primary ovarian insufficiency. Thus, regulating the assembly of mRNAs and RNA-binding proteins into discrete granules appears to provide important functions at both cellular and physiological levels. Here we review our current understanding of the role of post-translational modifications in regulating the condensation of RNA-binding proteins in the germ line. We compare and contrast the in vitro evidence that methylation inhibits phase separation of RNA binding proteins, with the extent to which these results apply to the in vivo germ line environment of several model systems. We also focus on the role of phosphorylation in modulating the dynamics of RNP granules in the germ line. Finally, we consider the gaps that exist in our understanding of the role of post-translational modifications in regulating germ line RNP granules.